2019
DOI: 10.5004/dwt.2019.23842
|View full text |Cite
|
Sign up to set email alerts
|

Removal of ammonia nitrogen, nitrate, phosphorus and COD from sewage wastewater using palm oil boiler ash composite adsorbent

Abstract: Sewage treatments are introduced in the country to protect the health of human and environment. In this study, palm oil fuel ash (POFA) was explored as an adsorbent media for the treatment of a sewage wastewater. The optimum shaking speed, shaking time, pH, and dosage for chemical oxygen demand (COD), ammonia nitrogen, nitrate and phosphorus removal were investigated using the adsorbent media of particle sizes ranging from 2.00 to 3.15 mm. POFA and composite POFA chemical composition and characteristics were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Slabbert [59] characterized and identified five metal complexes formed by iron (Fe +2 ), aluminum (Al +3 ), titanium (Ti), and molybdenum (Mo) ions. The metal complexes increased the charged transfer and enhanced the adsorption and deposition of dissolved heavy metals in water [59,60,61,62,63]. The removal of selected heavy metals from leachate under the obtained optimum experimental conditions (tannin dosage 0.75 g, pH 6, 250 rpm for 15 min followed by 60 rpm for 30 min and settling for 30 min) was investigated, and the results are presented in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…Slabbert [59] characterized and identified five metal complexes formed by iron (Fe +2 ), aluminum (Al +3 ), titanium (Ti), and molybdenum (Mo) ions. The metal complexes increased the charged transfer and enhanced the adsorption and deposition of dissolved heavy metals in water [59,60,61,62,63]. The removal of selected heavy metals from leachate under the obtained optimum experimental conditions (tannin dosage 0.75 g, pH 6, 250 rpm for 15 min followed by 60 rpm for 30 min and settling for 30 min) was investigated, and the results are presented in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…Despite all, the carbon has some health risks. The reported studies demonstrated that toxic effect is depends on morphology of nanoadsorbents, chemical stabilizers and surface modifications [160,161]. So, there is a need to give an attention to synthesize more stable morphology (size and shape) to overcome the toxicity issues as well as health risks.…”
Section: Nanosorbentsmentioning
confidence: 99%
“…At the beginning of the phytoremediation treatment, the average reading of NH 3 -N was high. This is due to the decomposition of organic solid matter by the existing bacterial reaction in the sewage wastewater sample [50,51]. Ammonia is one of the important nutrients for Centella asiatica to grow.…”
Section: Reduction Rate Of Codmentioning
confidence: 99%